AGE-RELATED ARTICULATORY VARIATIONS OF ARABIC /dˤ/: ACOUSTIC ANALYSIS IN ELDERLY NON-NATIVE SPEAKERS - Tanzil Nurholis; Mohamad Zaka Al Farisi; Nalahuddin Saleh (Universitas Islam Sumatera Utara (UISU), 2026)
Age-related decline in speech motor control affects older adults’ ability to pronounce Arabic phonemes accurately. While prior studies examined working-age native speakers, this study addresses non-native older adults to map the specific articulatory challenges they face in pronouncing /dˤ/ and investigate aging's effect on acoustic stability. We employed descriptive and comparative phonetic analysis, evaluating four older adults (ages 51–73) with varying educational backgrounds (Islamic boarding, elementary, junior high, and senior high schools). Data were acoustically compared to native speaker standards using Praat software to measure the duration, fundamental frequency, intensity, and formant patterns of /dˤ/ in initial, medial, and final word positions. Findings indicate that Islamic boarding school education does not ensure later-life articulatory precision; rather, overcompensation led to velarization failure due to prolonged articulation. In contrast, participants with junior and senior high school backgrounds produced acoustic qualities closer to native speakers. Although motor limitations restrict airflow endurance, cognitive retention of articulation points remains well-preserved. Ultimately, none of the elderly participants matched native speaker standards due to physiological decline rather than phonological memory loss. Consequently, evaluations of elderly Quranic recitation should emphasize articulation point accuracy rather than energetic performance.